Democracy and Oversight - PELIZZO, Riccardo (Institutional Knowledge at Singapore Management University, 2006)
In the course of the past decade, political science has started paying increasing attention to the study of legislative oversight, which had been previously been described as an important but inadequately researched area of legislative activity (Lees, 1977). Lees’ comment is particularly true with regard to comparative analyses of oversight tools and practices. Some studies have recently discussed the instruments of legislative oversight (Maffio, 2002), other studies have instead investigated how legislative oversight relates to both political variables (Pennings, 2000; Damgaard, 2000; Pelizzo and Stapenhurst, 2004a) and socio-economic conditions (Pelizzo and Stapenhurst, 2004b). In spite of this renewed interest in the study of oversight, our understanding of legislative oversight, as Rockman LAMented more than two decades ago (1984), is asymmetric. The literature has discussed extensively what oversight is, why it is necessary in properly functioning democratic regimes, why it is good from a normative point of view and what conditions might favor effective oversight. Yet, less attention has been paid to whether legislative oversight has any impact on the functioning of a political system and, if so, what kind of impact it has.